Supplementation with high-GABA-producing Lactobacillus plantarum L5 ameliorates essential tremor triggered by decreased gut bacteria-derived GABA - Hao-Jie Zhong; Si-Qi Wang; Ruo-Xin Zhang; Yu-Pei Zhuang; Longyan Li; Shuo-Zhao Yi; Ying Li; Lei Wu; Yu Ding; Jumei Zhang; Xinqiang Xie; Xing-Xiang He; et al. (Translational Neurodegeneration, 2023)
Abstract Background The γ-aminobutyric acid (GABA) hypothesis posits a role of GABA deficiency in the central nervous system in the pathogenesis and progression of essential tremor (ET). However, the specific causative factor for GABA deficiency is not clear. The gut microbiota in mammals has recently been considered as a significant source of GABA. Furthermore, the GABA-based signals originating from the intestine can be transmitted to the brain through the “enteric nervous system–vagus nerve–brain” axis. However, the plausible contribution of gut microbiota to ET seems inspiring but remains obscure. Methods Fecal samples from patients with ET and healthy controls were examined by metagenomic sequencing to compare the composition of gut microbiota and the expression of genes involved in GABA biosynthesis. The impact of gut microbiota on ET was explored through transplantation of fecal microbiota from patients with ET into the murine ET model. Lactic acid bacteria producing high amounts of GABA were identified through whole-genome sequencing and ultra-performance liquid chromatography-tandem mass spectrometry. Subsequently, mice were treated with the high-GABA-producing strain Lactobacillus plantarum L5. Tremor severity, behavioral tests, pro-inflammatory cytokines, GABA concentration, and gut microbiota composition were examined in these mice. Results The gut microbiota of patients with ET demonstrated an impaired GABA-producing capacity and a reduced fecal GABA concentration. Transplantation of the gut microbiota from patients with ET induced an extension of tremor duration and impaired mobility in the murine model of ET. L5 exhibited an augmented GABA-producing capacity, with the De Man-Rogosa-Sharpe culture broth containing 262 mg/l of GABA. In addition, administration of L5 significantly decreased the tremor severity and enhanced the movement capability and grasping ability of ET mice. In vivo mechanistic experiments indicated that L5 reshaped the gut microbial composition, supplemented the mucosa-associated microbiota with GABA-producing capacity, increased the GABA concentrations in the cerebellum, and diminished inflammation in the central nervous system. Conclusions These findings highlight that deficiency of GABA-producing gut microbes plays an essential role in the pathogenesis of ET and that L5 is a promising candidate for treating ET.